Hydrogen Bonded Supramolecular Structures - Li, Zhanting (Springer, 2015)
This book covers the advances in the studies of hydrogen-bonding-driven supramolecular systems made over the past decade. It is divided into four parts, with the first introducing the basics of hydrogen bonding and important hydrogen bonding patterns in solution as well as in the solid state. The second part covers molecular recognition and supramolecular structures driven by hydrogen bonding. The third part introduces the formation of hollow and giant macrocycles directed by hydrogen bonding, while the last part summarizes hydrogen bonded supramolecular polymers.